Juridical Analysis of Land Sale and Purchase Transactions that are not Equipped with Certificates in Grobogan Regency Region - Rio Marshel Sahertian; Diana Setiawati (Universitas Muhammadiyah Surakarta, 2025)
The primary objective of this study is to scrutinize and evaluate the process of transferring ownership rights to land lacking certification and its associated legal implications, while also assessing the proactive measures taken by National Land Agency Grobogan Regency in addressing instances of uncertified land transactions. Employing an empirical juridical research approach, which entails analyzing real world social issues to acquire pertinent knowledge for resolution, this study seeks to gain insights into the subject matter. Findings from the research indicate that the transfer of ownership rights to uncertified land in Grobogan Regency can occur through both formal and informal channels. These factors are influenced, among other things, by incomplete land documentation, the high cost of sale and purchase deeds, the still strong legal culture of local communities, and the low level of legal knowledge of local communities to carry out effective sales and purchases in accordance with government regulations. The legal consequence of owning uncertified land in the Globogan Regency area is that it is detrimental to the party holding the rights to the land because there is no guarantee of legal certainty. National Land Agency Grobogan Regency's approach to addressing instances of land transactions lacking certificates involves implementing a free land registration program, also known as Complete Systematic Land Registration (PTSL) by the National Land Agency. This initiative aims to streamline the registration process, particularly for rural communities, thereby ensuring legal certainty and protecting community land rights. Embracing principles such as simplicity, affordability, efficiency, safety, fairness, equity, transparency, and accountability, the program aims to facilitate accessible and fair land registration procedures.